PEMBENTUKAN KURVA IMBAL HASIL (YIELD) DENGAN MODEL NELSON SIEGEL-SVENSSON (NSS) (Studi Kasus Data Obligasi Pemerintah Periode 27 Oktober 2014 Sampai 31 Oktober 2014) - Hutahayan, Eugenia Septri; Widiharih, Tatik; Wilandari, Yuciana (Jurnal Gaussian, 2015)
Medium-term debt to long-term contains a promise from the issuer to pay interest in return for a certain period and repayment of the principal debt at a specified time to the purchaser bonds are called Bonds. A method to determine the relationship between the yield (yield) were obtained with the time to maturity for a particular type of bond at a given time is described by the yield curve (yield curve). One method to describe the yield curve is the Nelson Siegel Svensson. Observed data from the Bursa Efek Indonesia (BEI) that the data of Surat Utang Negara (SUN) with code FR (Fixed Rate). In this case the entire SUN FR with a yield is not empty in the period October 27, 2014 to October 31, 2014. Construction of the yield curve on October 27, 2014, October 28, 2014 and October 30, 2014 to form the normal curve (Positive Yield Curve) while the date October 29, 2014 and October 31, 2014 to form the combined curve between the normal curve (Positive Yield Curve) and negative curves (Inverted Yield Curve).Keywords : bond, the yield curve, Government Securities, Nelson Siegel Svensson.